The Impact of Public Bus Service Quality on the Users’ Satisfaction: Evidence from a Developing Asian City - Nur Zaimah, Ubaidillah; Nur Haziqah, Sa'ad; Farhana, Ismail; Nordiana, Ahmad Nordin; Nur Nadhira, Baharuddin; Mohd Khairul Hisyam, Hassan (Pro Global Science Association, 2022)
In a country where there is a high level of car ownership, public buses are considered another mode of transport that is more sustainable. Despite that, there is a very low level of public bus ridership in Malaysia which questions the users’ satisfaction with its service quality. This study investigates the role of public bus service quality (tangibility, reliability, assurance, empathy, and responsiveness) by utilizing the SERVQUAL model for users’ satisfaction. A sample of 300 questionnaires was obtained from public bus users in Kota Samarahan, Sarawak, Malaysia as the case study area. Using Partial Least Square-Structural Equation Model, the results show that tangibility, reliability, and responsiveness are significant service quality factors that influence users’ satisfaction with public buses in the case study area. Of the factors, tangibility is considered the most critical factor that influences users’ satisfaction. This study provides imperative knowledge which will be advantageous for stakeholders specifically policy-makers, transport ministries, town planners, local authorities, and service operators in strategizing policies and plans that could encourage the public buses usage.